Pengaruh Konseling Teknik Menyusui yang Benar terhadap Perilaku Menyusui pada Ibu Post Partum - Nur Faridah Trisiyah; Dewi Novianty (STIKes Patria Husada Blitar, 2014)
Proper breastfeeding technique is a way to give milk to the baby with the mother's position and attachment of the baby in a proper way. Counseling is done so that mothers can open minded, realizing his own mistaken of perception that associated with breastfeeding, and then expected to change or correct the incorrect perception that breastfeeding can run more smoothly.The purpose of this research was to determine the effectiveness of proper breastfeeding technique counseling to the behavior of lactating mothers in post partum day 1-14.Method: Research design was pre- experimental design with one-group pre- post test design.. The sample was 16 post-partum mothers at BPS Eny Kustiyaningsih, Amd. Keb, who was collected using total sampling. The instrument used was a checklist.Result: The result used Wilcoxon Sign Rank Test showed Ï = 0.000 (Î± = 0.05). It could be concluded that there were significant effect proper breastfeeding technique counseling to the behavior of lactating mothers in post partum day 1-14. Discussion: It was expected that the results of the research could be use as reference for further research.